Protective Roles of Interferon‐γ in Cardiac Hypertrophy Induced by Sustained Pressure Overload. Issue 6 (19th March 2018) - Kimura, Akihiko; Ishida, Yuko; Furuta, Machi; Nosaka, Mizuho; Kuninaka, Yumi; Taruya, Akira; Mukaida, Naofumi; Kondo, Toshikazu
Abstract : Background: A clear understanding of the molecular mechanisms underlying hemodynamic stress‐initiated cardiac hypertrophy is important for preventing heart failure. Interferon‐γ (IFN‐γ) has been suggested to play crucial roles in various diseases other than immunological disorders by modulating the expression of myriad genes. However, the involvement of IFN‐γ in the pathogenesis of cardiac hypertrophy still remains unclear. Methods and Results: In order to elucidate the roles of IFN‐γ in pressure overload–induced cardiac pathology, we subjected Balb/c wild‐type (WT) or IFN‐γ‐deficient ( Ifng −/− ) mice to transverse aortic constriction (TAC). Three weeks after TAC, Ifng −/− mice developed more severe cardiac hypertrophy, fibrosis, and dysfunction than WT mice. Bone marrow–derived immune cells including macrophages were a source of IFN‐γ in hearts after TAC. The activation of PI3K/Akt signaling, a key signaling pathway in compensatory hypertrophy, was detected 3 days after TAC in the left ventricles of WT mice and was markedly attenuated in Ifng −/− mice. The administration of a neutralizing anti‐IFN‐γ antibody abrogated PI3K/Akt signal activation in WT mice during compensatory hypertrophy, while that of IFN‐γ activated PI3K/Akt signaling in Ifng −/− mice. TAC also induced the phosphorylation of Stat5, but not Stat1 in the left ventricles of WT mice 3 days after TAC. Furthermore, IFN‐γ induced Stat5 and Akt phosphorylation in rat cardiomyocytes cultured under stretch conditions. A Stat5 inhibitor significantly suppressed PI3K/Akt signaling activation in the left ventricles of WT mice, and aggravated pressure overload–induced cardiac hypertrophy. Conclusions: The IFN‐γ/Stat5 axis may be protective against persistent pressure overload–induced cardiac hypertrophy by activating the PI3K/Akt pathway.